Polysemy in the Asilulu Language of Ureng Village, Leihitu District, Central Maluku Regency, Maluku Province - Pakay, Gita Febriani; Syahrir, Muhsyanur; Sasabone, Carolina; Hukubun, Yohanis (JENDELA PENGETAHUAN, 2025)
This research aims to describe polysemy in the Asilulu language in Ureng Village, Leihitu District, Central Maluku Regency. The type and method used is a descriptive qualitative research approach. The research data is in the form of polysemy in the Asilulu language. The data sources consist of 6 people, including Village Chiefs, Youth Heads, Education Leaders, Religious Leaders, Traditional Leaders, and Traders. Data collection techniques consist of observation, recording, interviews and documentation. The instruments used were observation sheets, interview guides, recording tools and documentation. Data analysis used a flow analysis model consisting of data collection, data reduction, data presentation, and drawing conclusions. To check the validity of the data, triangulation techniques were used. The research results show that there are people's utterances that contain polysemous words in the form of basic words and derivative words based on threeword classes, namely verbs, nouns and adjectives.